An Extubation Protocol for Angioedema. Issue 1 (February 2017) - Floyd, Elizabeth; Goldstein, Nira A.; Joks, Rauno; Mascaro, Miguel; Liaw, Christine; Dickson, Bradley; Varughese, Denny; Silverman, Joshua
Angioedema—nonpitting edema of the mucous membranes and skin—most commonly occurs as a complication from the use of angiotensin-converting enzyme inhibitors. At our institution, the otolaryngology department has incorporated the use of the endotracheal tube cuff-leak test and bedside direct laryngoscopy to aid in timing for extubation of angioedema patients. Prospective data collection of patients presenting to the emergency department with angioedema was performed. Of 76 patients with angioedema, 9 required fiberoptic intubation. Intubation was performed at a median of 73 hours (range, 44-118). An endotracheal tube cuff-leak test was performed in 7 patients prior to extubation, and bedside direct laryngoscopy was also performed in 3 of these 7 patients to document resolution of laryngeal edema. The use of the endotracheal tube cuff-leak test and bedside direct laryngoscopy is an easy and inexpensive method to help determine eligibility for extubation in patients intubated for angioedema.